The Level of Sense of Place in Inpres Market - Karsono, Bambang; Rekha Putri, Khana; Olivia, Sisca; A, Hendra (Malikussaleh University, Aceh, Indonesia, 2022)
Physical intervention in a market area tends to change user habits in responding to the space. This situation can ruin the authenticity of the sense of place and the loss of local identity for generations. This study aims to reveal the authenticity and understanding of the Inpres Market, a traditional market in Lhokseumawe. Re-development has been carried out at the Inpres Market to improve the layout of the stalls, change the architectural form of the building with a contemporary image, and increase the floor of the building vertically into two levels. Apprehensively this physical intervention will erode the meaning of place that has been attached to people's memories for a long time. This study must be conducted before any other new physical intervention occurs for any renovation or revitalization reason. This study is place-based research by choosing Inpres Market in Lhokseumawe as the case study. The research variable uses physical (tangible) and social (intangible) variables to reveal the sense of place in the market. The data was obtained using quantitative and qualitative methods, while the analysis was carried out in an exploratory, descriptive manner. The data collection method was conducted in two stages: observation, interviews, and questionnaires. The second stage of data collection involved 134 respondents, and a random sampling method was implemented to determine the respondents. The results showed that physical and social variables' influence in creating a sense of place is revealed.